2019
DOI: 10.1126/sciadv.aaw1228
|View full text |Cite
|
Sign up to set email alerts
|

Lysostaphin and BMP-2 co-delivery reduces S. aureus infection and regenerates critical-sized segmental bone defects

Abstract: Staphylococcus aureus is the most common pathogen associated with bacterial infections in orthopedic procedures. Infections often lead to implant failure and subsequent removal, motivating the development of bifunctional materials that both promote repair and prevent failure due to infection. Lysostaphin is an anti-staphylococcal enzyme resulting in bacterial lysis and biofilm reduction. Lysostaphin use is limited by the lack of effective delivery methods to provide sustained, high doses of enzyme to infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
81
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 51 publications
1
81
0
Order By: Relevance
“…49,[71][72][73] This enzyme has been shown to act on both biofilms and resistant strains of bacteria (Figure 3). 71 The attractiveness of lysostaphin is heightened by its ability to work synergistically with other therapeutics such as BMP-2 (for bony defect healing), 74 endolysins, 49,75 and some antibiotics. 76 Lysostaphin's efficacy may be attributed to its rapid action, which aids the initial attack by antibiotics on bacteria and helps increase efficacy.…”
Section: Enzymesmentioning
confidence: 99%
See 1 more Smart Citation
“…49,[71][72][73] This enzyme has been shown to act on both biofilms and resistant strains of bacteria (Figure 3). 71 The attractiveness of lysostaphin is heightened by its ability to work synergistically with other therapeutics such as BMP-2 (for bony defect healing), 74 endolysins, 49,75 and some antibiotics. 76 Lysostaphin's efficacy may be attributed to its rapid action, which aids the initial attack by antibiotics on bacteria and helps increase efficacy.…”
Section: Enzymesmentioning
confidence: 99%
“…101,109 Hydrogels are generally biodegradable and may be cleared by the body in as early as 2 to 6 weeks. 101,105,109 Hydrogels have been used as carriers for antibiotics, 103,105,108,110,111 bacteriophages, 34,42,47,106 and proteins, 42,49,71,74 as well as nanoparticles and microparticles containing therapeutics. 94,105,110 One of the advantages of hydrogels is the ability to tailor their properties including porosity, viscosity, elasticity, degree of swelling, and rate of drug elution.…”
Section: Hydrogelsmentioning
confidence: 99%
“…The ability of bacteriophage‐delivering hydrogels to heal these bone defects will be the subject of future studies. We note our recent study demonstrating that lysostaphin/BMP‐2‐delivering hydrogels eliminated S. aureus infection and supported full bone defect repair at 8 weeks in the same murine segmental model (Agarwal et al, ; Johnson et al, ).…”
Section: Discussionmentioning
confidence: 54%
“…Biomaterial platforms to deliver antimicrobial agents, such as antibiotics and antimicrobial peptides, or present polymers with bactericidal properties have emerged as powerful technologies to combat infection (Caplin & García, ). For example, we recently reported on synthetic hydrogels with controlled delivery of the antimicrobial enzyme lysostaphin that eliminate bone infections and promote the repair of bone fractures and nonhealing segmental bone defects (Johnson et al, ; Johnson et al, ). Although very promising, this strategy is limited to Gram‐positive staphylococcal species.…”
Section: Discussionmentioning
confidence: 99%
“…Considerable research has focused on the factors that may promote bone formation or affect the proliferation and differentiation of osteoblasts. For example, bone morphogenetic protein‐2 can promote bone formation and has been combined with various delivery carriers in bone regeneration practice . The role of the mechano‐growth factor (MGF) Ct24E was investigated in bone formation and remodeling, which showed that MGF‐Ct24E has a marked ability to increase bone formation by increasing cell proliferation and delaying cell differentiation .…”
Section: Discussionmentioning
confidence: 99%